Semantic Interpretations of Proper Names in Literary Translation: Terry Pratchett’s “Wyrd Sisters” in Bulgarian - Manova-Georgieva, Yana (English Studies at NBU, 2022)
Name crafting has been and still is of importance when devising a literary character with certain traits and features that are meant to outstand a character’s personality. Thus, literary names serve as a handy tool in any piece of writing, since they complete their bearers in a discrete, yet a vivid way when given an appropriate name by the author of a piece of writing. As far as fantasy is concerned, the choice of literary names is freer, but still requires more creativity, given the fact that fantasy names can be translated. When rendered from one language into another, names undergo various structural alterations, semantic modulations, or even syntactic reconstructions. Therefore, the current paper aims at analysing literary names in Terry Pratchett’s fantasy novel “Wyrd Sisters” with focus on their rendering into Bulgarian. Etymology and semantic interpretations are to be sought for as well as morphological and syntactic structure of names in both languages of interest in favour of the hypothesis that literary names carry meaning which, when revealed, gives a more concrete idea of a personage in a novel.